Estudo da economia de energia proveniente do controle inteligente de iluminação aplicando parâmetros da certificação LEED: estudo de caso - Scarsi, Victor Hugo Evangelista (2019)
Brazil is among the countries that invest the most in sustainable construction in the world, named as the 4th country in the world ranking. Thus, intelligent automation systems become great allies in the pursuit of energy efficiency and sustainability, as they are used, for example, for lighting and air conditioning control, which represent a large part of building's energy consumption. There are several organizations that award certifications for sustainable buildings at various levels, proving pre-established methods and models, where the LEED certification (Leadership in Energy and Environmental Design) is one of the main international. In the present study, the premises of the LEED certification, Energy and Atmosphere section with O+M typology in Existing Buildings, are taken as basis, in order to prove the need and aid of automation systems for an intelligent and sustainable environment, highlighting, in particular, strategies for lighting control. A case study of the FAE Business School’s building, situated in Curitiba, Paraná, which is not LEED certified, but has been carried out and has been investing in intelligent optimization technologies for automation in a building with 20 classrooms, among others, to ensure a better use of energy and comfort to users. Applying LEED certification criteria, the Energy Star Portfolio Manager tool was used to obtain the average building data, which is adopted as a reference for comparisons. The results of the study show that the classrooms of this building consume 72 % less energy than similar buildings, due to the intelligent light control system installed in the building. It was concluded to achieve LEED certification with a minimum score, the studied building must fulfill a series of improvements and prerequisites. Thus, it’s possible to achieve between 25 % and 90 % of the LEED score required for certification, only in the typology evaluated by this paper.